Pengaruh Pajak Daerah dan Retribusi Daerah terhadap Pertumbuhan Ekonomi dengan Pendapatan Asli Daerah Sebagai Variabel Intervening di Kabupaten Sidoarjo Tahun 2016-2021 - Alifia Dina Rifai; Hero Priono (Universitas Batanghari Jambi, 2022)
This study aims to examine the effect of local taxes and local retribution on economic growth, using local own-source revenue as an intervening variable in Sidoarjo Regency in 2016-2021. This type of research is quantitative. The data used is secondary data with data collection techniques using documentation techniques. The sample selection method in this study used the saturated sampling method. The data analysis technique used in this research is to use SmartPLS 3.0. The result of this research is that local taxes and local retribution have no effect on economic growth. local taxes and local retribution have an effect on local own-source revenue. Local own-source revenue has an effect on economic growth. Local own-source revenue cannot mediate the effect of local taxes and local retribution on economic growth